2012
DOI: 10.1002/jbio.201200132
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry, histopathology and infrared spectral histopathology of colon cancer tissue sections

Abstract: During the past years, many studies have shown that infrared spectral histopathology (SHP) can distinguish different tissue types and disease types independently of morphological criteria. In this manuscript, we report a comparison of immunohistochemical (IHC), histopathological and spectral histopathological results for colon cancer tissue sections. A supervised algorithm, based on the "random forest" methodology, was trained using classical histopathology, and used to automatically identify colon tissue type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 41 publications
2
141
0
Order By: Relevance
“…27 If mucin associated changes can be characterized using such technology at cellular level, it could provide vital information related to the characteristics of cancers being investigated. Previous IR spectroscopy studies on colon tissues were undertaken to identify the abnormalities in colon epithelial regions [4][5][6] and the secreted mucin 7 as potential indicators of cancer. These were carried out using the conventional IR set ups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 If mucin associated changes can be characterized using such technology at cellular level, it could provide vital information related to the characteristics of cancers being investigated. Previous IR spectroscopy studies on colon tissues were undertaken to identify the abnormalities in colon epithelial regions [4][5][6] and the secreted mucin 7 as potential indicators of cancer. These were carried out using the conventional IR set ups.…”
Section: Resultsmentioning
confidence: 99%
“…IR spectroscopy can provide information about these variations that can be used to identify, understand and in some cases even predict the possibility of the occurrence of a disease. In this regard, IR spectroscopy has been investigated as a potential cancer diagnostic tool in various tissue types including some highly prevalent cancers such as lung, 2 colon, [3][4][5][6][7] oral cavity, 8 liver, 9 prostate, [10][11][12] breast, [13][14][15] lymphnode, 16,17 cervix, 18 etc. Using IR spectroscopic imaging approaches, biological material can be imaged to obtain bio-molecular information, where each pixel of the image constitutes a spectrum with a specific bio-molecular signature.…”
Section: Introductionmentioning
confidence: 99%
“…A paper by Hartsuiker et al [73] reported results indicating that Raman imaging of individual cells could distinguish cultured cells overexpressing this gene. In addition, a recent paper by Kallenbach et al [77] indicated that regions of high p53 and Ki67 activity, detected via IHC fluorescence microscopic imaging, correlated well with regions of specific IR signatures. Thus, we may expect that SHP data, when analyzed properly, may provide information on cancer type, cancer grade, and presence of certain prognostic markers in one measurement that presently require several separate procedures (H & E, IHC), and are less subjective in nature.…”
Section: Diagnosis Of Cervical Sqcc and Cervical Adc Via Shpmentioning
confidence: 94%
“…Alternatively, one can assess the overall accuracy of the classifier. 6 However, this technique can be misleading for many tissue types. For example, classification of all pixels in a breast biopsy as collagen will likely lead to a high classification rate.…”
Section: Resultsmentioning
confidence: 99%
“…Exciting results using FT-IR imaging have been reported by a number of other groups including ourselves. [5][6][7][8][9] We have also previously shown cell-type segmentation using FT-IR imaging in a number of tissues including prostate and breast. 4, 10…”
Section: Ft-ir Imagingmentioning
confidence: 97%